Caracterização de complexos de transferência de carga entre íons derivados de N,N'-alquildiil-bis(piridínio substituídos) com iodeto - Carvalho, Fernando Rodrigues de (2011)
Charge Transfer Complexes (CTC) were first defined by Mulliken who have proposed the theory which suggests that in this type of complex electrons donor (D) and acceptor (A) interactions are involved. As a result of D-A interaction, an additional band in the UV-Vis electronic absorption spectra region appears, which does not correspond to the individual absorption of D and A. In the present work, the class of acceptor compounds that we are interested are pyridinium derivatives, heterocyclic and biologically active molecules present in relevant biological systems, NAD+ and NADP+. Indeed, pyridinium cations has also been used to biomimetic systems; the synthetic versatility enables synthesize pyridinium derivatives with different molecular designs allowing its use as a local probe in order to study the physical chemical properties of membranes and colloids. On the other hand, considering the electron donor compounds, iodide I- is an n-donor, electron donor n. The results demonstrated a charge transfer band of the CTC formed between the acceptors studied (ions N,N'-alkyldiil-bis(4-cyanopyridinium) Cnbis(4CP)2+ dimers bridged by n methylene chain (spacers) with n= 3, 4, 6 and 8 units; the ions N,N'-alkyldiil-bis(2- bromopyridinium) Cnbis(2BP)2+ dimers with n = 4 and 6 methylene groups and ions N-alkyl- 4-cyanopyridinium Cn4CP+ monomers where n = 4, 6 and 16 refers to the number of carbons on the alkyl group (R) and the ion N-alkyl-2-bromopyridinium Cn2BP+ monomer where n = 1, methyl group) and iodide as electron donor. The 1:1 stoichiometry, and the KCTC and εCTC values were determined. These results indicated that dimers derivatives form a "sandwich type-complex" with iodide and that either as the KCTC as εCTC increase when n decrease, or increase from monomers to dimers. This trends were confirmed by two methods (Benesi-Hildebrand and iteractive) and by fluorescence quenching Stern-Volmer measurements having iodide as a suppressor and pyridine derivatives as fluorophore. In all cases, this trends stems from the intensifying of the positive charge density and "sandwich" effect as n decreases, and, they increase from monomers to dimers. Through the solvent study was verified that the CTC formation are favored in low dielectric constant solvents. These are also favored with temperature increasing, indicating a spontaneous complexation process however endothermic being driver by the entropic factor. Water and anions SCN-, Br - act as interfering species in complex formation. Therefore pyridine derivatives could be used in the spectrophotometric iodide determination in the mmol.L-1 order. The spectroscopic parameters were calculated for the systems Cnbis(4CP)2+/I - and indicated that the CTC formed are extremely stable and its stability increases as n decreases, confirming the trend obtained in the KCTC, εCTC e ΔGº values. The ionization potential of SCN- , Br - and I- ions has been calculated and found that the latter has lower ionization potential in a given solvent and that the ionization potential of I - decreases as the dielectric constant decreases indicating that iodide is a better electron donor in non-polar solvents. The electrochemical results show a characteristic redox peak for the CTC studies, which is dependent on the chain methylenes bound between pyridine rings (n) and donor type.